Parental marital quality and children's depression in China: the different mediating roles of parental psychological aggression and corporal punishment - Tian, Wenxiu (Journal of family violence, 2023)
Previous studies have shown that depression is a serious public health problem among children, and it is necessary to explore the causes and potential mechanisms of depression in children. Therefore, this study examined the relationship between parental marital quality and children’s depression and the mediating effects of parental harsh discipline—psychological aggression and corporal punishment—in China. The participants were 735 primary school students from grades 5–6 and their parents in Chinese families. Participants completed a series of questionnaires measuring marital quality, harsh discipline and children’s depression. Two path analysis models—one for fathers and the other for mothers—were constructed. The findings indicated that maternal but not paternal marital quality was negatively and directly associated with children’s depression. Both fathers’ and mothers’ psychological aggression mediated the associations between parental marital quality and children’s depression, while fathers’ and mothers’ corporal punishment did not. The findings from this study imply that interventions for decreasing children’s depression should not only focus on improving maternal marital quality but also target fathers’ and mothers’ harsh discipline, especially psychological aggression.